High Performance Liquid Chromatography of Amino Acids Using Potentiometric Detector With A Tungsten Oxide Electrode - Yeni Maulidah Muflihah; Zulfikar Zulfikar; Siswoyo Siswoyo; Asnawati Asnawati; Qurrota Ayun (UNEJ e-Proceeding, 2016)
High Performance Liquid Chromatography (HPLC) method combine with potentiometric detector was applied as a method for analysis of amino acids (aspartic acid, glutamic acid and arginine). The separation was carried out on a C18 column with isocratic elution of  a mixture of acetonitrile and phosphat buffer. Potentiometric detector using a tungsten oxide electrode as working electrode and Ag/AgCl as refference electrode. The detection method was based on the presence of H+ ions from amino acids. This application was a development of previous studies that was succesfully applied to detect the presence of amino acids in batch and flow systems. Amino acid determination was characterized by its retention time. Retention time of aspartic acid, glutamic acid and arginine were as follow: 8,46; 13,0; and 15,21 minutes. The optimized separation conditions obtained at a flow rate of 1,2 mL/min with 15% acetonitrile concentration, buffer pH 6,5 with phosphat concentration of 5x10-4 M. Detector performance tested by the recovery test of samples, and the results obtained for glutamic acid, aspartic acid and arginine respectively: 89,1%, 94,9%, and 110%. Linear range obtained at 10-3 M to 10-7 M.  Detection limit were 1,58x10-7 M for glutamic acid, 6,58x10-8 M for aspartic acid and 6,51x10-8 M for arginine.